(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Khan MN, Ali S, Razak SA, Zaman A, Iqbal M, Shah SN. 2021. Assessment of floristic diversity in the mountain ecosystem of Marghazar Valley, Hindukush Range, Swat, Pakistan. Biodiversitas 23: 1000-1013. Marghazar Valley, a part of the Hindukush Range, is an area with a rich diversity of plant resources. Geo-climatically and ecologically, this valley is characterized by a moist temperate and subtropical zone with a Sino-Japanese type of vegetation. A comprehensive survey was carried out from April 2019-June 2020 to explore the biodiversity and ecological aspects of plants in Marghazar Valley, Swat District, Khyber Pakhtunkhwa, Pakistan. The study recorded a total number of 307 taxa (161 herbs, 45 shrubs, 46 trees, 37 grasses, 10 climbers, 2 shruby herbs, 1 subshrub, 1 tree-like herb, 1 hollow tufted tree, 1 climbing shrub, 1 parasitic herb and 1 woody climber) belong to 94 families and 236 genera that consisted of Pteridophytes (14 species, 9 genera, 7 families), Gymnosperms (5 species, 4 genera, 2 families) and Angiosperms (288 species, 223 genera and 85 families). Families with the highest number of species were Poaceae (38 species) and Asteraceae (29 species), followed by Rosaceae (22 species), Brassicaceae (13 species) and Lamiaceae (11 species), while the rest of the families had less than 11 species. Dicots were the group with the largest number of genera (75.24 %), followed by Monocots (18.56 %), Pteridophytes (4.54 %) and Gymnosperms (1.62 %). Cousinia bupthalmoides was recorded from the area for the first time and are a novel addition to the flora of Swat. Phenology of vegetation revealed that 173 taxa (56.35%) recorded as perennial followed by 134 taxa as annual plants (43.50%). Bio-spectrum classes were represented by 126 species as therophytes (40.90%) and 122 species as microphylls (39.61%) in life form and leaf size respectively, while 2 species i.e Cuscuta reflexa and Equisetum arvense are aphyllus which possesses no leaves.